2014
DOI: 10.1371/journal.pntd.0003344
|View full text |Cite|
|
Sign up to set email alerts
|

Spatiotemporal Transmission Dynamics of Hemorrhagic Fever with Renal Syndrome in China, 2005–2012

Abstract: BackgroundHemorrhagic fever with renal syndrome (HFRS) is a rodent-borne disease caused by many serotypes of hantaviruses. In China, HFRS has been recognized as a severe public health problem with 90% of the total reported cases in the world. This study describes the spatiotemporal dynamics of HFRS cases in China and identifies the regions, time, and populations at highest risk, which could help the planning and implementation of key preventative measures.MethodsData on all reported HFRS cases at the county le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 39 publications
2
59
0
Order By: Relevance
“…Although China has recorded what were likely hantavirus infections in ancient literature, dating back to the 12 th century (Song, 1999), HFRS was first clinically recognized in 1931 in northeast China (Zhang WY et al, 2014). HFRS first came to the attention of western physicians when 3,200 United Nations troops fell ill in Korea between 1951and 1954(Schmaljohn and Hjelle, 1997.…”
Section: Diseases Caused By Hantavirus and The Reservoirs Hemorrhagicmentioning
confidence: 99%
See 2 more Smart Citations
“…Although China has recorded what were likely hantavirus infections in ancient literature, dating back to the 12 th century (Song, 1999), HFRS was first clinically recognized in 1931 in northeast China (Zhang WY et al, 2014). HFRS first came to the attention of western physicians when 3,200 United Nations troops fell ill in Korea between 1951and 1954(Schmaljohn and Hjelle, 1997.…”
Section: Diseases Caused By Hantavirus and The Reservoirs Hemorrhagicmentioning
confidence: 99%
“…In China, HFRS is classified as a class B notifiable disease (Zou et al, 2016) and is considered a severe public health challenge (Zhang WY et al, 2014;Jiang et al, 2016). HTNV and SEOV are the major causes of HFRS (Song, 1999;Zhang S et al, 2014).…”
Section: Asian-pacific Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicated that the geographical distribution of HFRS incidences was clustered, particularly in the northeastern, central and eastern parts of China. The observed hotspots shifted and expanded from year to year, whereas most HFRS cases were mainly reported during the spring and the autumn-winter seasons [14][15][16]. In these studies, global indicators of spatial autocorrelation (GISA), local indicators of spatial association (LISA) and Kulldorff 's scan statistic were employed to characterize the spatial variation of HFRS incidence during several time periods.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 HFRS is highly endemic in east Asia, with over 20,000 cases per year with mortality rates ranging from 1% to 15%. 6 The isolation and whole-genome sequencing of HTNV are required for the development of anti-viral strategies and the understanding of hantavirology.…”
Section: Introductionmentioning
confidence: 99%